Management of labor pain with alternative therapies: literature review - Casa Toaquiza, Nancy María; Lascano Sánchez, Adriana del Rocío (Enfermería Cuidándote, 2026)
Introduction: Childbirth marks a crucial moment in a woman’s reproductive life and is directly related to pain, which is intense and inevitable. Each woman experiences it differently; there are even differences between births within the same woman. The application of alternative and complementary therapies contributes to a calmer and more satisfying experience, generating maternal and fetal well-being. Objective: To analyze the management of labor pain with alternative therapies based on scientific evidence. Methodology: A literature review was conducted in databases such as PubMed, Dialnet, Scielo, and Redalyc following PRISMA guidelines. In addition, studies published between 2019 and 2024, written in English and Spanish, were included. Results: Thirteen articles were analyzed, the subject of which was to identify the most commonly used alternative therapies that reduce pain during labor, the results of the application of different alternative techniques in previous studies, and their benefits against pain. Among them, hydrotherapy, breathing exercises, aromatherapy, music therapy, Swiss balls, and support contributed to well-being and satisfaction for the mother-child relationship. Conclusion: Various studies show that alternative and complementary therapies are much more effective when applied during the first stage of labor, considered the most painful and prolonged. However, further research is needed to determine their effectiveness in the second and third stages of labor.